Preparation of Cobalt Nanoparticles - Khusnuriyalova, Aliya F.; Caporali, Maria; Hey‐Hawkins, Evamarie; Sinyashin, Oleg G.; Yakhvarov, Dmitry G. (European journal of inorganic chemistry, 2021)
The development of modern chemistry is currently proceeding in several priority areas including investigations focused on the synthesis, stabilisation, and application of transition metal nanoparticles (NPs), which are widely used in physical, chemical, engineering, and biomedical processes. A special place among known transition metal NPs is occupied by cobalt nanoparticles, since they are used for highly important targets, such as creation of new catalysts, magnetic devices, composites, or carriers for drug delivery. The selective preparation of NPs is a difficult task that requires special conditions and has some limitations. In this minireview, we summarise the most successful and most efficient methods for obtaining Co NPs, including chemical and physical aspects of their preparation. The various practically useful chemical and physical properties of cobalt nanoparticles (Co NPs) attract a huge interest from the specialists working in different research and industrial fields. However, the selective preparation of Co NPs is a difficult task that requires special conditions and apparatus. This minireview summarises the most successful and useful methods for obtaining Co NPs, including the relevant chemical and physical aspects.